Parametric Studies in Push-Over Analysis - LAM, TAN SOCK (UNIVERSITI TEKNOLOGI PETRONAS, 2014)
API Recommended Practice 2A-WSD is widely used in the industry to design fixed offshore platform. The design parameters in the API standards are used in all fixed offshore platform design. However, the effect of changing these design parameters upon offshore platform still remains unclear. Hence, the objective of this study is to identify the impact of design parameters on the serviceability of the offshore platforms. Besides, a trend regarding the changes of the design parameter is established to ease the further study on this matter. A push-over analysis is carried out on the selected platform based on the changed parameters. The Reserve Strength Ratio is calculated to determine the strength of the selected platform. From the result, it is safe to mention that the lower the grad of the steel used, the lower the strength of the platform. Besides that, the CdCm values are most optimum at 0.65 and 1.60 respectively. However, an increase of 20% of CdCm values shows interesting changes in the strength of the platform. Further study can be carried out regarding this aspect. Moreover, lower the allowable corrosion thickness, the lower the strength of the platform. Last but no least, the changes in the platform weight do not gives a significant change of the selected offshore platform.